Ozone depletion in the Arctic and Antarctic stratosphere induced by wildfire smoke - Ansmann, Albert; Ohneiser, Kevin; Chudnovsky, Alexandra; Knopf, Daniel A.; Eloranta, Edwin W.; Villanueva, Diego; Seifert, Patric; Radenz, Martin; Barja Gonzalez, Boris; Zamorano Banda, Felix De La Cruz; Jimenez, Cristofer; Engelmann, Ronny; et al. (My University, 2022)
A record-breaking stratospheric ozone loss was observed over the Arctic and Antarctica in 2020. Strong ozone depletion occurred over Antarctica in 2021 as well. The ozone holes developed in smoke-polluted air. In this article, the impact of Siberian and Australian wildfire smoke (dominated by organic aerosol) on the extraordinarily strong ozone reduction is discussed. The study is based on aerosol lidar observations in the North Pole region (October 2019-May 2020) and over Punta Arenas in southern Chile at 53.2 degrees S (January 2020- November 2021) as well as on respective NDACC (Network for the Detection of Atmospheric Composition Change) ozone profile observations in the Arctic (Ny-Alesund) and Antarctica (Neumayer and South Pole stations) in 2020 and 2021. We present a conceptual approach on how the smoke may have influenced the formation of polar stratospheric clouds (PSCs), which are of key importance in the ozone-depleting processes. The main results are as follows: (a) the direct impact of wildfire smoke below the PSC height range (at 10-12 km) on ozone reduction seems to be similar to well-known volcanic sulfate aerosol effects. At heights of 10-12 km, smoke particle surface area (SA) concentrations of 5-7 mu m(2) cm(-3) (Antarctica, spring 2021) and 6-10 mu m(2) cm(-3 )(Arctic, spring 2020) were correlated with an ozone reduction in terms of ozone partial pressure of 0.4-1.2 mPa (about 30 % further ozone reduction over Antarctica) and of 2-3.5 mPa (Arctic, 20 %-30 % reduction with respect to the long-term springtime mean). (b) Within the PSC height range, we found indications that smoke was able to slightly increase the PSC particle number and surface area concentration. In particular, a smoke-related additional ozone loss of 1-2 mPa (10 %-20 % contribution to the total ozone loss over Antarctica) was observed in the 14-23 km PSC height range in September-October 2020 and 2021. Smoke particle number concentrations ranged from 10 to 100 cm(-3) and were about a factor of 10 (in 2020) and 5 (in 2021) above the stratospheric aerosol background level. Satellite observations indicated an additional mean column ozone loss (deviation from the long-term mean) of 26-30 Dobson units (9 %-10 %, September 2020, 2021) and 52-57 Dobson units (17 %20 %, October 2020, 2021) in the smoke-polluted latitudinal Antarctic belt from 70-80 degrees S.
Keywords: Ozone Depletion